EFEKTIFITAS KERJA APARATUR PEMERINTAH DALAM RANGKA PELAYANAN PUBLIK DI KECAMATAN WORI KABUPATEN MINAHASA UTARA - RACHMAN, ISMAIL (Sam Ratulangi University, 2016)
Abstract: Public service is the main task of the civil servant. The demand of the community to improve thequality of service is very strong nowadays. The society as the main character in implementation of thedevelopment is expected to take part actively in the process. Therefore, the business environment should beconducive with fast serving, accountable and safe.Service for the civil servant is very important because the government is the thinker, planner and executor ofthe development. Also as the supporter for the society; as the servant; control the society; encourage thesociety’s participation; educate the society and being responsive to the society’s aspiration.To determine the work effectiveness, which involve with public service, therefore can be determined with someindicators such as a. Level of education b. Discipline of the civil servant c. the ability of the servant to carry thetask and responsibility d. ability in technology.Keywords: Work Effectiveness, Government Apparatus and Public Service